Analytical Method Development and Validation of RP-HPLC Method for Estimation of Levothyroxine in Bulk and Pharmaceutical Dosage Form - Shaikh, Afiya; Kanase, Krunal; Veer, Vikram; Bhosale, Ashok (Journal of Neonatal Surgery, 2025)
Objective: To develop and validate a simple, accurate, and robust RP-HPLC method for the estimation of levothyroxine in bulk drug and pharmaceutical dosage forms, ensuring compliance with regulatory quality standards. Method: A reverse-phase high-performance liquid chromatography (RP-HPLC) method was developed using a C18 column (250 mm × 4.6 mm, 5 µm) with a mobile phase of phosphate buffer (pH 3.0) and methanol (55:45 v/v). The flow rate was set at 1.0 mL/min, detection wavelength at 225 nm, and injection volume was 10 µL. The method was validated as per ICH Q2(R1)1guidelines. Result: The method exhibited excellent linearity in the range of 0.08–0.8 µg/mL with a correlation coefficient (r²) of 0.999. Accuracy was within 95–105%, precision (%RSD) was less than 2%, LOD was 0.03 µg/mL, and LOQ was 0.09 µg/mL. The method also demonstrated strong specificity and robustness. Conclusion: The validated RP-HPLC method is simple, sensitive, precise, and suitable for the routine quality control and stability analysis of levothyroxine sodium in pharmaceutical formulations, meeting all regulatory validation criteria.